2010
DOI: 10.1186/1476-4598-9-291
|View full text |Cite
|
Sign up to set email alerts
|

ZNF217 confers resistance to the pro-apoptotic signals of paclitaxel and aberrant expression of Aurora-A in breast cancer cells

Abstract: BackgroundZNF217 is a candidate oncogene located at 20q13, a chromosomal region frequently amplified in breast cancers. The precise mechanisms involved in ZNF217 pro-survival function are currently unknown, and utmost importance is given to deciphering the role of ZNF217 in cancer therapy response.ResultsWe provide evidence that stable overexpression of ZNF217 in MDA-MB-231 breast cancer cells conferred resistance to paclitaxel, stimulated cell proliferation in vitro associated with aberrant expression of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 39 publications
4
55
0
Order By: Relevance
“…These cell lines have been described to show resistance to PTX (37)(38)(39). We confirmed that PTX had almost no effect on TS/ApGL3 cell viability and reduced MDA-MB-231 and MDA-MB-231-ZNF217rvLuc2 cell viability by only 30% to 40% over 24 to 48 hours, relative to vehicle control ( Supplementary Fig.…”
Section: Pyr1 Treatment Decreases Breast Cancer Cell Proliferation Insupporting
confidence: 61%
“…These cell lines have been described to show resistance to PTX (37)(38)(39). We confirmed that PTX had almost no effect on TS/ApGL3 cell viability and reduced MDA-MB-231 and MDA-MB-231-ZNF217rvLuc2 cell viability by only 30% to 40% over 24 to 48 hours, relative to vehicle control ( Supplementary Fig.…”
Section: Pyr1 Treatment Decreases Breast Cancer Cell Proliferation Insupporting
confidence: 61%
“…Furthermore, ZNF217 has a demonstrated role in promoting proliferation in several models of breast cancer. Specifically, silencing of ZNF217 results in reduced proliferation in several breast cancer cell lines (including MCF-7), and overexpression of ZNF217 increases proliferation in the same cell lines as well as in xenograft tumors (Thollet et al 2010). The established role of ZNF217 as an oncogene combined with these findings strongly support miR-503 as a candidate tumor suppressor in breast cancer.…”
Section: The Role Of Mir-503 and Znf217 In Cellular Proliferation Andsupporting
confidence: 49%
“…In this study, we identify three major patterns of gene expression following estrogen stimulation: (i) transient, (ii) induced, and (iii) repressed. Among the genes repressed by estrogen stimulation is the oncogene ZNF217, which has been shown to enhance proliferation in ovarian ) and breast cancer (Thollet et al 2010). Additionally, we have shown that the estrogen-induced miRNA, miR-503, targets the 3 ′ -UTR of ZNF217 and that while miR-503 is induced in response to estrogen, the oncogene ZNF217 is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…MDA-MB-231-pcDNA6, ZNF217-1, and ZNF217-2 cells have been described previously (11). Populations of MCF10A-pcDNA6 and MCF10A-ZNF217 stable transfectants were obtained using the same plasmid and selection process as described in Thollet and colleagues (11).…”
Section: Znf217 Stable Transfectantsmentioning
confidence: 99%
“…Previous studies have found that high levels of ZNF217 expression have been associated with resistance to chemotherapy and with deregulated apoptotic signals in breast cancer cells (10,11). The precise molecular mechanisms involved in ZNF217 prosurvival functions are currently unknown, but activation of the Akt pathway (10), ErbB3 overexpression (12), Aurora-A overexpression (11), deregulated expression of several members of the Bcl-2 family (11), eEF1A2 overexpression (13), and interaction with the HIF pathway (14) have been proposed.…”
Section: Introductionmentioning
confidence: 99%